INTRODUCING CHILDREN TO NATURE AS A PEDAGOGICAL PROCESS: A MULTIDISCIPLINARY APPROACH - Toshtemirova Dilnura (International Scientific and Current Research Conferences, 2023)
This thesis explores the significance of introducing children to nature as a pedagogical process, recognizing the critical role nature plays in a child's holistic development. The study emphasizes the benefits of nature-based pedagogy, incorporating a multidisciplinary approach to enhance children's cognitive, emotional, social, and physical development. The research evaluates the impact of nature exposure on academic performance, mental well-being, environmental awareness, and overall lifelong learning. Additionally, the thesis proposes practical strategies and recommendations for educators and parents to effectively integrate nature into children's learning experiences.